Philosophy of Psychology: Causality and Psychological Subject New Reflections on James Woodward's Contribution - Gonzalez, Wenceslao J. (Epistemic Studies ;, 2018)
Contemporary philosophy of science analyzes psychology as a science with special features, because this discipline includes some specific philosophical problems - descriptive and normative, structural and dynamic. Some of these are particularly relevant both theoretically (casual explanation) and practically (the configuration of the psychological subject and its relations with psychiatry). Two central aspects in this book are the role of causality, especially conceived as intervention or manipulation, and the characterization of the psychological subject. This requires a clarification of scientific explanations in terms of causality in psychology, because characterizations of causality are quite different in epistemological and ontological terms. One of the most influential views is James Woodward's approach to causality as intervention, which entails an analysis of its characteristics, new elements and limits. This means taking into account the structural and dynamic aspects included in causal cognition and psychological explanations. Psychology seen as special science also requires us to consider the scientific status of psychology and the psychological subject, which leads to limits of naturalism in psychology.